CDK4/6 inhibitors in advanced hormone receptor-positive breast cancer - Barroso-Sousa, Romualdo; Tolaney, Sara M. (Translational Cancer Research, 2017)
Approximately 70% of breast cancers (BC) are classified as hormone receptor-positive (HR-positive), comprising those expressing estrogen receptors and/or progesterone receptors. BC deaths are ultimately caused by metastatic disease. In this setting, although estrogen pathway blockade is an initially highly effective therapy, virtually all patients will develop resistance to endocrine therapy (de novo or acquired). Further understanding of the underlying mechanisms related to endocrine therapy resistance is vital and can ultimately lead to new therapies for this population. Recently, cyclin-dependent kinase (CDK) 4/6 inhibitors have emerged as one of the most important groups of drugs that synergize with endocrine therapy. In this perspective article we will discuss the recent data from the phase III MONALEESA-2 trial, which evaluated the addition of ribociclib with letrozole in the first line of treatment for patients with advanced HR-positive BC, and we will put the results in context with clinical data of other CDK 4/6 inhibitors. In addition, we will discuss future directions in the field.